The thickness of time: the writing of history and appropriation of the past in Brazil, 1830-1930 - Mollo, Helena; Turin, Rodrigo; Nicolazzi, Fernando (Historein, 2018)
The recent Brazilian history of historiography perceives the period from 1830 to 1930 as a decisive one for the development of Brazilian historiography, be it for the definition of the disciplinary protocols that frame the historian’s work or for the emergence of problems concerning the disputes over and elaboration of a national identity. The importance of this century has already been established in works on the role of national institutions, such as the Brazilian Historical and Geographical Institute (IHGB) and the National Museum, and in works on the discursive dimensions of historiographical practice. Thus, a new way to consider the experience of time has been proposed, resulting in a thoughtful understanding of the history of historiography and its field. Therefore, this article aims to offer an overview of the different modulations of temporal experience that appear in nineteenth- and early twentieth-century Brazilian historiography, presenting some of the topoi that have organised and shaped it.